Invisible electronics: Metastable Cu-vacancies chain defects for highly conductive p-type transparent oxide. (December 2017) - Lunca Popa, Petru; Crêpellière, Jonathan; Nukala, Pavan; Leturcq, Renaud; Lenoble, Damien
Graphical abstract: Highlights: P-type transparent semiconductor with conductivity around 100 S cm −1 is reported. Cu-vacancies chains are evidenced as p-type doping source. Thermal treatment reveals the metastable nature of the defects. Abstract: Non-stoichiometric copper chromium delafossite has lately attracted a high interest in the community of oxide materials due to its high p-type electrical conductivity and adequate transparency in the visible range. This study reports record electrical conductivity of Cu0.66 Cr1.33 O2 thin films deposited by chemical vapour deposition and investigates their properties. As-deposited samples show conductivities greater than 100 S cm −1 and carrier concentrations around 10 21 cm −3, highest reported value for any non-intrinsically doped delafossite system. A new structural defect consisting in Cu-vacancies chains is identified. This defect, never observed or presumed before, heals upon annealing at 900 °C under argon environment, resulting in an electrical conductivity's reduction of six orders of magnitude. Through a wide-range of structural, chemical and transport measurement techniques, a structure-defect-property correlation of this system is established and the metastability of the non-stoichiometry induced defects is investigated. The possibility of manipulating the defects and carrier concentrations through high-temperature annealing and the outstanding electrical properties associated with the large-scale deposition technique and moderate deposition temperature could be of great technological interest. This material could find important applications as hole injection or extraction layer in all-oxide photovoltaic and light emitting devices.